2017
DOI: 10.1063/1.5004649
|View full text |Cite
|
Sign up to set email alerts
|

Optimal stretching in the reacting wake of a bluff body

Abstract: We experimentally study spreading of the Belousov-Zhabotinsky reaction behind a bluff body in a laminar flow. Locations of reacted regions (i.e., regions with high product concentration) correlate with a moderate range of Lagrangian stretching and that range is close to the range of optimal stretching previously observed in topologically different flows [T. D. Nevins and D. H. Kelley, Phys. Rev. Lett. 117, 164502 (2016)]. The previous work found optimal stretching in a closed, vortex dominated flow, but this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…the formation of biofilm, dissolution and precipitation patterns), and shed new light on the notion of optimal stretching observed also in other flows (Nevins & Kelley 2016; Wang et al. 2017). For example, the stretching-induced mixing enhancement shown in this study is closely related to the reactant blowout observed in Nevins & Kelley (2016).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…the formation of biofilm, dissolution and precipitation patterns), and shed new light on the notion of optimal stretching observed also in other flows (Nevins & Kelley 2016; Wang et al. 2017). For example, the stretching-induced mixing enhancement shown in this study is closely related to the reactant blowout observed in Nevins & Kelley (2016).…”
Section: Discussionmentioning
confidence: 71%
“…Hence, fluid stretching promotes mixing and enhances reaction rates. Interestingly, two recent experimental studies have reported that there are optimal ranges of fluid stretching for maximum reactivity if the reaction systems are with an excitation threshold such as the Belousov-Zhabotinsky reaction (Nevins & Kelley 2016;Wang et al 2017). The authors found reaction blowout at high stretching rates, and this blowout is explained qualitatively by the dilution of the reactant due to the fluid stretching.…”
Section: Introductionmentioning
confidence: 99%
“…The third device is a water channel that produces a wake behind a bluff body, previously described in detail. 21 The bluff body is an equilateral triangle with a side length of 45 mm, positioned symmetrically about the channel center with one vertex pointing upstream. The channel flow is dominated by shear (not vorticity) except in the wake behind the bluff body.…”
Section: Experimental Advection-reaction-diffusion Devicesmentioning
confidence: 99%
“…Second, other barriers to front propagation may also be possible, and front tracking could locate them. For example, recent studies 20,21 have found that excitable reactions are promoted mostly in regions where the Lagrangian stretching falls in an optimal range. Outside this range, fronts propagate slowly, or are driven to extinction by a process analogous to blowing out a flame.…”
Section: Summary and Future Workmentioning
confidence: 99%
See 1 more Smart Citation